PENGARUH PROMOSI JABATAN DAN MUTASI KERJA TERHADAP SEMANGAT KERJA MELALUI KEPUASAN KERJA PADA PT. PEGADAIAN KANWIL VI MAKASSAR - Rahmat, Nuzul; Tangisalu, Jannati; Ampauleng, Ampauleng (Jurnal Bina Bangsa Ekonomika, 2025)
Pegadaian Regional Office VI Makassar is part of PT. Pegadaian (Persero) which has an important role in supporting the economy in its region. As a financial institution that focuses on financing and various services, PT. Pegadaian has a great responsibility in providing the best service to the community and creating a conducive business climate. In the face of increasingly fierce competition, quality human resources (HR) are the key to the company's success. Employees who have high work morale can make a positive contribution to the achievement of the company's goals.  The method used in this study is an explanatory method with a quantitative research approach and primary data sources. Meanwhile, to analyze the data obtained, Multiple Linear Regression Analysis, Coefficient of Determination Analysis, and Hypothesis Test with the help of smartPLS were used. Based on the results of the study, it was explained that job promotion had a significant positive effect on work morale, work mutation had a significant positive effect on work morale, Job promotion had a significant positive effect on job satisfaction, job mutation had a significant positive effect on job satisfaction, job satisfaction had a significant positive effect on work morale, Position promotion had a non-significant positive effect on work morale through job satisfaction and work mutations have a positive and insignificant effect on work morale through job satisfaction